Electron scattering from the molecular hydrogen ion and its isotopologues - Zammit, Mark; Fursa, Dmitry; Bray, Igor (American Physical Society, 2014)
We have extended the ab initio convergent close-couplingmethod to electron scattering from the vibrationallyexcited molecular hydrogen ion and its isotopologues. Calculations have been performed within the adiabaticnucleiapproximation. Results are presented for dissociative excitation and ionization as a function of the initialvibrational state of the molecules. Comparison with experiment is excellent across the energy range from nearthreshold to 1 keV.